Collaboration between case managers and family caregivers in a context of integrated care for the frail elderly - Couturier, Yves (Igitur, Utrecht Publishing & Archiving, 2010)
PURPOSE: Case management is a human device which’s purpose is to enhance the quality of services by improving their coordination. However, the case manager is not the sole bearer of the coordination duty; the first line medical doctor, the service user himself and his family caregiver may also contribute. The family caregiver represents a very important coordinator whose contribution to case management remains feebly recognized. This communication focuses on the family caregiver’s contribution to the general coordination of services. THEORY: Even though few studies have focused on family caregivers’ roles in services’ coordination, their role is recognized as crucial. Diverse models of the family caregiver’s role will be utilized to orientate our analysis of their contributions to general coordination. METHODS: Employing an embedded case study design, we conducted 18 paired interviews with user/caregiver dyads (six in three different integrated care networks) following a method aimed at making explicit their concrete coordination practices. RESULTS AND CONCLUSIONS: Services’ coordination is marked by a delay between the emergence of a clinical need and the implementation of a service, which is partially compensated by the family caregiver. Hence, global coordination is temporally out of phase with the user’s needs.